Primary spinal epidural non‐Hodgkin's diffuse large B‐cell lymphoma: A case report. Issue 11 (21st September 2020) - Pokhrel, Nishan Babu; Prasad, Rohit; Paudel, Sushil; Kafle, Dinesh; Pokharel, Rohit Kumar
Abstract: Rare disease like primary spinal epidural diffuse large B‐cell lymphoma should be considered as a differential diagnosis in patients presenting with back pain and rapid neurological deterioration in the lower extremities. Abstract : Rare diseases like primary spinal epidural diffuse large B‐cell lymphoma should be considered as a differential diagnosis in patients presenting with back pain and rapid neurological deterioration in the lower extremities.